2014
DOI: 10.1136/annrheumdis-2014-eular.2420
|View full text |Cite
|
Sign up to set email alerts
|

OP0238 Suppression of T Cell Activation and Collagen Accumulation by an Anti-Type I Interferon Receptor Monoclonal Antibody in Adult Subjects with Systemic Sclerosis

Abstract: Background MEDI-546 is an investigational human IgG1κ monoclonal antibody directed against subunit 1 of the type I interferon receptor (IFNAR1). An open-label single- and multiple-dose phase 1a clinical trial has been conducted for MEDI-546 in adult systemic sclerosis (SSc) subjects (NCT00930683). Objectives To identify serum markers and pathophysiological pathways modulated by MEDI-546 in SSc subjects. Methods Affymetrix whole genome arrays were used to measure transcript expression in whole blood and ski… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In this model, we combined the macromolecular crowding with dermal fibroblasts and translational biomarkers. It has previously been reported that biomarkers of type I, III and VI collagen formation are elevated in SSc patients [25][26][27][28] . In the current study, we show that this pre-clinical model may be used for screening potential drugs.…”
Section: Discussionmentioning
confidence: 99%
“…In this model, we combined the macromolecular crowding with dermal fibroblasts and translational biomarkers. It has previously been reported that biomarkers of type I, III and VI collagen formation are elevated in SSc patients [25][26][27][28] . In the current study, we show that this pre-clinical model may be used for screening potential drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphocyte involvement in fibrosis is under investigation. In systemic sclerosis, patients subjected to a therapy based on anifrolumab, a monoclonal antibody targeting IFN‐α and ‐β receptors, undergo suppression of T‐lymphocyte activation and a decrease in collagen accumulation (39).…”
Section: Purinergic Modulation Of the Immune System In Wound Healing mentioning
confidence: 99%